Evaluation of wheat cultivars for drought resistance during germinating - Amin, Aumeed Noori M.; Tawfik, Shirwan Ismail (Sulaimani Journal for Pure and Applied Sciences, 1999)
Cultivars seeds of T. durum and T. aestivum were tested for their potential germination under drought stress conditions. Seeds of aestivum c.v.'s were more drought stress resistant that durum c.v.'s seeds. In addition, aestivum seed germinate faster thatn durum under high stress conditions. Cultivars were differ in their respond to different moisture stress conditions.